The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1093/eurjhf/hfq227
|View full text |Cite
|
Sign up to set email alerts
|

Volume reduction rate by surgical ventricular restoration determines late outcome in ischaemic cardiomyopathy

Abstract: AimsSurgical ventricular restoration (SVR) effectively reduces left ventricular (LV) volume in ischaemic cardiomyopathy (ICM), but the recent Surgical Treatment of Ischemic Heart Failure (STICH) Trial questions its importance. We report 8-year SVR experience in patients with ICM. Methods and resultsBetween 2000 and 2008, 135 patients underwent SVR for ICM. This report analyses data from 90 patients who underwent accurate pre-and post-operative assessment of LV volumes by left ventriculogram or scintigram. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…More recently, we have suggested the effectiveness of SVR for patients with ICM 51) . According to our results, SVR is most effective when a >33% volume reduction rate achieves an LVESVI of <90 ml/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…More recently, we have suggested the effectiveness of SVR for patients with ICM 51) . According to our results, SVR is most effective when a >33% volume reduction rate achieves an LVESVI of <90 ml/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…However, in the Surgical Treatment for Ischemic Heart Failure (STICH) trial, adding surgical ventricular restoration (SVR) to coronary artery bypass grafting (CABG) did not result in any improvement in survival or ventricular function, even though SVR achieved greater LV end-systolic volume index (LVESVI) reduction, by 19% as a whole, as compared to the 6% achieved with CABG alone 2) . As a benchmark 30% post-SVR volume reduction, which could impact the prognosis, has been reported 3) , a 19% volume reduction seems to be modest. Many subanalyses of the STICH results have been performed, and it has become clear which patient group has benefitted the most from SVR.…”
Section: Introductionmentioning
confidence: 95%
“…Isomura et al 3) performed a retrospective analysis of 135 ischemic cardiomyopathy patients who underwent SVR. They concluded that SVR is most effective when a >33% volume reduction rate achieves an LVESVI of <90 ml/m 2 , and no long-term benefits occur when SVR induces an LV volume reduction of <15%, leaving a residual LVESVI >90 ml/m 2 .…”
Section: Volumementioning
confidence: 99%
“…2 In fact, the postoperative LV end-systolic volume index (ESVI) <60 ml/m 2 , a >30% ESVI reduction, and >33% ESVI reduction with a resultant postoperative ESVI <90 ml/m 2 are considered to be desired goals of SVR, since these are associated with lower mortality rates after SVR. [3][4][5] On the other hand, the postoperative ESVI <70 ml/m 2 could demarcate candidates for SVR, because this is associated with a higher survival rate for those with CABG plus SVR than those with CABG alone. 4 However, the volume reduction effect by SVR has limits.…”
Section: Introductionmentioning
confidence: 99%